A comparative study on the lipid peroxidation and total antioxidant status in patients with and without varicose veins - Shetty, Gaurav B.; Ballal, Rajesh; Kumari N., Suchetha; Ullal, Harshini (International Journal of Research in Medical Sciences, 2016)
Background: The prevalence of varicose veins was increasing with increasing age but a deviance from the normal prevalence of the female patients. The patho- physiology has yet not been clearly delineated but the role of certain enzymes leading to oxidative stress has been implicated in the causation of this disease. Therefore, the present study was conducted to compare the lipid peroxidation and total antioxidant status in the patients with and without varicose veins. Methods: This study was performed after the institutional ethical clearance and informed consent from all the participants. Patients who were admitted for the surgery of inguinal Hernia were taken as controls. The blood was obtained and its serum was used for the estimation of MDA, GPx, and total antioxidant status using commercially available kit, according to the manufacturer’s guidelines in the central research laboratory of the institute. The data was represented as Mean±S.D. and compared using students‘t’ test and a p value of <0.05 was considered the level of significance. Results: The Serum estimations of MDA, GPX and TAC on comparison to Normal Individuals did not show any statistical significance (p>0.05). Conclusions: The levels of MDA, GPX and TAC were at the upper limit of the normal ranges in patients of Varicose veins indicating that more on antioxidants as a measure of global stress index in varicose veins are needed to be performed in the future with different Antioxidants and Advent of investigative modalities for the same.